ChemInform Abstract: Synthesis, Antimicrobial and Cytotoxicity Study of 1, 3‐Disubstituted‐1H‐naphtho[1, 2‐e][1, 3]oxazines. Issue 12 (14th March 2013) - Verma, Vikas; Singh, Kuldeep; Kumar, Devinder; Klapoetke, Thomas M.; Stierstorfer, Joerg; Narasimhan, Balasubramanian; Qazi, Asif Khurshid; Hamid, Abid; Jaglan, Sundeep
Abstract A series of novel symmetrically (II) as well as unsymmetrically (VI) diaryl‐substituted 1H‐naphtho[1, 2‐e][1, 3]oxazines are synthesized and screened for their antimicrobial and cytotoxic activities.